URGENSI PENEGAKAN HUKUM HAK CIPTA TERHADAP PEMBUAT KONTEN DALAM PENGGUNAAN LAGU DI MEDIA SOSIAL - Langit Rafi Soemarsono; Rianda Dirkareshza (JURNAL USM LAW REVIEW, 2021)
This paper aims to examine and examine how the law is enforced against content creators in the use of songs on social media. The normative juridical legal research method uses an analytical approach using the provisions of the legislation that are relevant to the issues discussed. The results of the study show that one of the phenomena that is quite often found on the internet, especially on various social media platforms, is copyright infringement committed by content creators in reproducing and publishing copyrighted songs belonging to songwriters or musicians, without realizing the importance of the rules of economic and social rights. moral rights related to song copyright. Due to the rampant violations that occur regarding copyright, especially regarding songs, there are not a few roles of musicians or songwriters who want reforms related to copyright regulations, especially in the use of song works on social media. As for in this study, it will discuss what forms of copyright infringement are carried out by content creators in the use of songs on social media and how the form of law enforcement for content creators in the use of social media songs. That based on the results of the analysis, it can be concluded that it is important to make government regulations specifically regarding copyright provisions in the use of songs on social media which are related to economic rights and moral rights.